Study of business ethics in occupational medicine. Issue 5 (May 1997) - Philipp, R; Goodman, G; Harling, K; Beattie, B
Abstract : OBJECTIVE: To investigate the views of specialists in occupational medicine about business ethics in occupational medicine. METHOD: A qualitative study with face to face focus groups and successive reviews of the draft consensus was undertaken of all accredited specialists in occupational medicine who were members of the south Wales and west of England group of the Society of Occupational Medicine, and of all regional specialty advisers and deputies from the Faculty of Occupational Medicine. RESULTS: There was widespread agreement for the need of a code of business ethics. In all, during the four draft stages of preparing a consensus, 72% (28/39) of members of the south Wales and west of England group of the Society of Occupational Medicine, and 31% (20/64) of regional specialty advisers and deputies provided detailed comment for inclusion in it. CONCLUSIONS: Consensus of their views was reached among study participants for issues of business ethics involving advertising, competence, qualifications, fees, commitment, changes in provider contracts, regulation, and supervision of trainees. It provides a basis for further debate.